Hb Gibbon [β124(H2)Pro→Thr (HBB: c.373C>A, p.P125T)], an Asymptomatic Novel Hemoglobin Variant Detected by Newborn Screening. (4th May 2019) - Wolf, Alejandro; Rohr, Joseph M.; Amador, Catalina; Starr, Lois J.; Hoyer, James D.; Ford, James B.
Abstract: We describe here a previously unreported hemoglobin (Hb) variant, Hb Gibbon [β124(H2)Pro→Thr ( HBB : c.373C>A, p.P125T)] detected by newborn Hb screening in a term male with no family history for hemoglobinopathy or other screening abnormalities. This missense mutation produces a β-globin chain variant that was detected by high performance liquid chromatography (HPLC) methods, but is silent by capillary electrophoresis (CE). DNA sequencing studies revealed that his father was also a heterozygote for this mutation. Neither has abnormalities on complete blood count (CBC) or any symptomatology.